Pengaruh Penerapan Model Problem Based Learning terhadap Hasil Belajar Siswa - Umayrah, Umayrah; Sripatmi, Sripatmi; Azmi, Syahrul; Arjudin, Arjudin (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2023)
This study aims to describe the application of the model problem-based learning as well as know the effect on student learning outcomes. This research is quantitative research using a true experimental type posttest-only control group design. The research population was class XI students of SMK Negeri 2 Mataram with a sample of class XI RPL 2 as the experimental class and XI RPL 1 as the control class which was selected by purposive sampling technique. Data collection techniques using test instruments. Data analysis techniques in the form of descriptive statistics and inferential statistics. The results of the study show: 1) there is a positive and significant influence from the application of the model problem-based learning on student learning outcomes, where the influence exerted is included in the large category with a significance value of 0.6 or with an influence percentage of 38.2%; 2) application of the model problem-based learning works well according to the steps on the model problem-based learning which includes: the stages of student orientation to problems, organizing students, guiding individual and group investigations, developing and presenting results, as well as analyzing and evaluating the process and results of problem-solving.